Inhibition of retinal neovascularization by a PEDF-derived nonapeptide in newborn mice subjected to oxygen-induced ischemic retinopathy. (June 2020) - Sheibani, Nader; Zaitoun, Ismail S.; Wang, Shoujian; Darjatmoko, Soesiawati R.; Suscha, Andrew; Song, Yong-Seok; Sorenson, Christine M.; Shifrin, Victor; Albert, Daniel M.; Melgar-Asensio, Ignacio; Kandela, Irawati; Henkin, Jack
Abstract: Retinopathy of prematurity (ROP) is a growing cause of lifelong blindness and visual defects as improved neonatal care worldwide increases survival in very-low-birthweight preterm newborns. Advancing ROP is managed by laser surgery or a single intravitreal injection of anti-VEGF, typically at 33–36 weeks gestational age. While newer methods of scanning and telemedicine improve monitoring ROP, the above interventions are more difficult to deliver in developing countries. There is also concern as to laser-induced detachment and adverse developmental effects in newborns of anti-VEGF treatment, spurring a search for alternative means of mitigating ROP. Pigment epithelium-derived factor (PEDF), a potent angiogenesis inhibitor appears late in gestation, is undetected in 25–28 week vitreous, but present at full term. Its absence may contribute to ROP upon transition from high-to-ambient oxygen environment or with intermittent hypoxia. We recently described antiangiogenic PEDF-derived small peptides which inhibit choroidal neovascularization, and suggested that their target may be laminin receptor, 67LR. The latter has been implicated in oxygen-induced ischemic retinopathy (OIR). Here we examined the effect of a nonapeptide, PEDF 336, in a newborn mouse OIR model. Neovascularization was significantly decreased in a dose-responsive manner by single intravitreal (IVT) injections of 1.25–7.5 μg/eye (1.0–6.0 nmol/eye). By contrast, anti-mouse VEGFA164 was only effective at 25 ng/eye, with limited dose-response. Combination of anti-VEGFA164 with PEDF 336 gave only the poorer anti-VEGF response while abrogating the robust inhibition seen with peptide-alone, suggesting a need for VEGF in sensitizing the endothelium to the peptide. VEGF stimulated 67LR presentation on endothelial cells, which was decreased in the presence of PEDF 336. Mouse and rabbit eyes showed no histopathology or inflammation after IVT peptide injection. Thus, PEDF 336 is a potential ROP therapeutic, but is not expected to be beneficial in combination with anti-VEGF. Highlights: PEDF-derived 9-mer peptide, PEDF 336, previously shown to inhibit laser-induced CNV in mice was tested in OIR. IVT injection of 1 μL PEDF 336 (1.25–7.5 μg) in neonatal mouse eyes at transition from 75% O2 to room air (P12) reduced NV and VO at P17. While PEDF 336 displayed dose-responsive efficacy, anti-mouse VEGFA164 was active only at 25 ng/eye, but not at half or twice this dose. Combination of both peptide and anti-VEGF showed only antibody efficacy but not robust peptide activity, thus the latter may require VEGF. PEDF 336 contains a 5-mer epitope, Y- - - R, that binds laminin receptor, 67LR, which increased on choroidal EC after exposure to VEGF.